The liver in times of COVID-19: What hepatologists should know - Ridruejo, Ezequiel (2020)
The ongoing pandemic of coronavirus disease 2019 (COVID-19) pandemic poses a serious threat to healthcare systems globally. Information regarding how the infection affects the liver and relevance of pre-existing liver disease as a risk factor for acquiring the infection or having a severe disease are still scarce. Also, considerations in liver transplant patients, those having hepatocellular carcinoma or under immunosuppressive therapy are being matter of analysis as information is being generated. Different treatments for COVID-19 are currently under study, some of which may be associated to hepatotoxicity. In the present review we discuss current data on the COVID-19 and liver, aiming to provide hepatologists with updated information to face this pandemic.